K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

29 tháng 11 2021
x=2 vì (2-1)^2=1^2=1
29 tháng 11 2021

( x - 1 )2 = 1                                                                                                                                                                            (x - 1)² =1                                                                                                                                                                             =) x - 1 = 1                                                                                                                                                                            x = 1 + 1 = 2

21 tháng 3 2020

\(\left(x+1\right)^2+\left(x^2+1\right)=0\)

\(\Leftrightarrow\orbr{\begin{cases}\left(x+1\right)^2=0\\\left(x^2+1\right)=0\end{cases}\Leftrightarrow\orbr{\begin{cases}x+1=0\\x^2+1=0\end{cases}\Leftrightarrow}\orbr{\begin{cases}x=-1\\x^2=-1\end{cases}\Leftrightarrow}x=-1}\)

Vậy x=-1

1) (X-6)x(2x - 6)=0

=> X - 6 = 0 => x = 0 + 6 = 6

=> 2x - 6 = 0 => 2x = 6 => X = 6 : 2 = 3

Vẫy x{6; 3}

2) 100:(x-7)=1

            x-7 = 100:1

            x-7 = 100

            x   = 100 + 7

            x   = 107 

6 tháng 1 2016

tinh tong cua 11,10,9,8,7,6,5,..........,-37,-38

-675 nha ban

2 tháng 9 2017

3+2x-1=24-[16-(4-1)]

3+2x+1=24-(16-3)

3+2x+1=24-13

3+2x+1=11

2x+1=11-3

2x+1=8

2x+1=23

=> x+1=3

x=2

2 tháng 9 2017

3+2\(^{x-1}\)=24-[16-3]

3+2\(^{x-1}\)=24-13=11

2\(^{x-1}\)=11-3=8=2\(^3\)

=>x-1=3

=>x=4

4 tháng 12 2016

X=4

k mk nha!!!!!

10 tháng 2 2020

x(x-1)-(x-1)2=0

<=> (x-1)[x-(x-1)]=0

<=> (x-1).1=0

<=> x-1=0

<=> x=1

10 tháng 2 2020

Ta có : x(x - 1) - (x - 1)2 = 0

=>   x2 - x - (x2 - 1) = 0

=>   x2 - x - x2 +1 = 0

=>   -x +1 = 0

=>   -x = -1

=>    x =1

9 tháng 1 2021

Ai đó giúp đi tôi chịu